Click Chemistry and Multicomponent Reaction for Linker Diversification of Zinc Dipicolylamine-Based Drug Conjugates - Tsai, Ching-Hua; Chiu, Tai-Yu; Chen, Chiung-Tong; Hsu, Chia-Yu; Tsai, Ya-Ru; Yeh, Teng-Kuang; Huang, Kuan-Hsun; Tsou, Lun Kelvin (Frontiers in Chemistry, 2022)
An efficient Ugi multicomponent reaction with strain promoted azide-alkyne cycloaddition protocol has been utilized in concert or independently to prepare a small family of bioactive zinc(II) dipicolylamine (ZnDPA)-based SN-38 conjugates. With sequential click chemistry coupling between the cytotoxic payload and phosphatidylserine-targeting ZnDPA ligand that derived from structurally diverse carboxylic acids, aldehyde or ketones, and isocyanides, we demonstrated this convergent synthetic strategy could furnish conjugates harnessing diversified linkers that exhibited different pharmacokinetic profiles in systemic circulation in vivo. Among the eight new conjugates, comparative studies on in vitro cytotoxicities, plasma stabilities, in vivo pharmacokinetic properties and maximum tolerated doses were then carried out to identify a potent ZnDPA-based SN-38 conjugate that resulted in pancreatic cancer growth regression with an 80% reduction of cytotoxic payload used when compared to that of the marketed irinotecan. Our work provided the roadmap to construct a variety of theranostic agents in the similar manner for cancer treatment.